Antitumour necrosis factor-α agents and development of new-onset cirrhosis or non-alcoholic fatty liver disease: a retrospective cohort. Issue 1 (15th April 2020) - Tang, Kuo-Tung; Dufour, Jean-François; Chen, Po-Hung; Hernaez, Ruben; Hutfless, Susan
Abstract : Objective: Elevated tumour necrosis factor (TNF)-α has been implicated in the progression of liver fibrosis and pathogenesis of non-alcoholic fatty liver disease (NAFLD). We aim to investigate the impact of anti-TNF-α agents on the development of cirrhosis and NAFLD. Design: This retrospective cohort study used a US claims database between 1 January 2010 and 31 December 2016. We identified adult patients with ankylosing spondylitis, inflammatory bowel disease, psoriatic arthritis or rheumatoid arthritis. Anti-TNF-α agents of interest included adalimumab, certolizumab, etanercept, golimumab and infliximab. The primary composite outcome was the development of new-onset cirrhosis, NAFLD or non-alcoholic steatohepatitis (NASH). The secondary outcomes were the development of (1) cirrhosis and (2) NAFLD or NASH. Propensity score for anti-TNF-α agent use was generated by logistic regression. Cox proportional hazard models adjusting for the propensity score were used with regard to time-varying anti-TNF-α agent exposure. Results: This study included 226 555 incident patients with immune-related diseases. During the median 1.5 years follow-up, there was an increased hazard with anti-TNF-α agent use in regard to liver outcomes (composite outcome HR: 1.47, 95% CI 1.27 to 1.70; cirrhosis HR 1.47, 95% CI 0.96 to 2.23; NAFLD or NASH HR 1.53, 95% CI 1.32 to 1.77). The composite outcome hazard was increased for each immune-related disease (HR 1.25–1.90). Conclusion: In the short term, we did not observe a beneficial effect of anti-TNF-α agent use for development of cirrhosis, NAFLD or NASH in patients with immune-related diseases.